Influence of tumour burden on trastuzumab pharmacokinetics in HER2 positive non‐metastatic breast cancer. (7th March 2016) - Bernadou, Guillemette; Campone, Mario; Merlin, Jean‐Louis; Gouilleux‐Gruart, Valérie; Bachelot, Thomas; Lokiec, François; Rezai, Keyvan; Arnedos, Monica; Diéras, Véronique; Jimenez, Marta; Paintaud, Gilles; Ternant, David
Abstract : Aims: Trastuzumab, an antibody binding to epidermal growth factor receptor‐2 (HER2), has been approved to treat HER2‐positive breast cancer in different settings. This study aimed at evaluating the influence of tumour size on trastuzumab pharmacokinetics (PK) in non‐metastatic breast cancer patients treated with short term pre‐operative trastuzumab. Methods: Trastuzumab PK data were obtained from a multicentre, randomized and comparative study. This antibody was administered pre‐operatively to patients with localized HER2‐positive breast cancer as a single 4 mg kg −1 loading dose followed by 5 weekly 2 mg kg −1 doses. Trastuzumab concentrations were measured repeatedly using an ELISA technique. Tumour size was evaluated at baseline using breast echography. Trastuzumab pharmacokinetics were studied using a population approach and a two compartment model. The influence of tumour burden on trastuzumab pharmacokinetics was quantified as a covariate. Results: A total of 784 trastuzumab concentrations were available from the 79 eligible patients. Estimated parameters (interindiviual standard deviation) were central volume of distribution =2.1 l (23%), peripheral volume of distribution =1.3 l (38%), intercompartment clearance =0.36 l day −1, with an elimination half‐life of 11.8 days. Typical clearance was 0.22 l day −1 (19%) and its value was increased with tumour size. In patients with the highest tumour size, trastuzumab clearance was 50% [18%–92%] higher than in patients with the lowest tumour size. Conclusions: In non‐metastatic breast cancer patients, trastuzumab clearance increases with tumour size. The elimination half‐life of trastuzumab was shorter in the present population of patients than in metastatic breast cancer patients previously studied.